2015
DOI: 10.1007/s10126-015-9625-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Shell Color-Related Genes in the Clam Meretrix meretrix

Abstract: Color polymorphism has received much attention due to its strong implications for speciation and adaptation. In contrast to body color, little is currently known about the molecular mechanism of shell color formation. This study represents the first analysis of the relationship between whole-scale gene expression and shell color variations in the marine bivalve mollusks via comparative transcriptome analyses. Three clam Meretrix meretrix strains with different and monotonous shell color patterns, which were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 54 publications
0
37
1
Order By: Relevance
“…To date, genomic and transcriptomic analysis of many other bivalve species focusing on the identification of candidate genes related to immunological defense (Ertl et al 2016; Moreira et al 2012; Nam et al 2016; Rao et al 2015), response to benzo (a) pyrene toxicity (Liu et al 2014b), shell color (Yue et al 2015), reproduction (Li et al 2016; Patnaik et al 2016; Teaniniuraitemoana et al 2014), and environmental stress (Milan et al 2011) in order to understand the biological mechanisms involved in the above factors. Recently, transcriptome analysis of R. philippinarum using 454 pyrosequencing technology revealed putative members of immunological defense genes involved in complement cascades, apoptosis, and the toll like signaling pathways (Moreira et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To date, genomic and transcriptomic analysis of many other bivalve species focusing on the identification of candidate genes related to immunological defense (Ertl et al 2016; Moreira et al 2012; Nam et al 2016; Rao et al 2015), response to benzo (a) pyrene toxicity (Liu et al 2014b), shell color (Yue et al 2015), reproduction (Li et al 2016; Patnaik et al 2016; Teaniniuraitemoana et al 2014), and environmental stress (Milan et al 2011) in order to understand the biological mechanisms involved in the above factors. Recently, transcriptome analysis of R. philippinarum using 454 pyrosequencing technology revealed putative members of immunological defense genes involved in complement cascades, apoptosis, and the toll like signaling pathways (Moreira et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…M. petechialis has a typical periostracum outside the calcified shell; the colour of this periostracum determines the colour of the shell (Yue et al 2015). Periostracum synthesis starts at the early stages of development, and the periostracum grows continuously over the entire life of the bivalve.…”
Section: Discussionmentioning
confidence: 99%
“…After a basic local alignment search tool (BLAST) analysis of the expressed sequence tag (EST) sequences from the cDNA library of Meretrix petechialis that we had previously constructed (Yue et al 2015), one EST sequence (~400 bp) showed the highest similarity to the laccase gene. The full-length laccase cDNA of M. petechialis (MpLac) was then obtained by using the rapid amplification of cDNA ends (RACE).…”
Section: Full-length Cdna Cloning and Sequence Analysismentioning
confidence: 99%
See 2 more Smart Citations